Faraidh dan Keadilan: Menelusuri Prinsip Pembagian Waris dalam Masyarakat Kontemporer - Dinda Putri Hasanah; Hanifah Hanifah; Royhana Safitri; Sri Mei Ulfani; Wismanto Wismanto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This article discusses the application of faraidh principles in the context of contemporary society, focusing on the challenges and solutions faced in inheritance distribution. The background of this research is based on the need to understand how the Islamic inheritance system can function amidst changing social dynamics, including the influence of local culture and gender inequality. The purpose of the study is to explore the community's understanding of faraidh, as well as to identify factors that influence the practice of inheritance distribution. The method used in this study is a qualitative method with a library research approach. The results of the study indicate that many individuals still have a knowledge gap regarding their rights in the faraidh system, which often results in inheritance. In addition, the influence of patriarchal culture and the weakness of formal education regarding inheritance law also contribute to injustice in the distribution of property. This study recommends the need for better education, the use of technology to access information, and collaboration between various parties to improve the understanding and application of faraidh principles. With these steps, the hope of justice in inheritance distribution can be realized effectively in society.